The phenomenon of Warren Buffett and the modern financial theory, or the role of image in Buffett’s investment strategy - ЧирковаЕлена Владимировна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
The article provides for an explanation of the Warren Buffett’s phenomenon, namely his ability to earn more than 20% on capital on an annualized basis during approximately 60 years. Modern financial theory gives no room for such an outcome. Attachment to value investing can not fully explain the phenomenon as many investors are well familiar with the concept yet nobody can replicate Buffett’s results. The author claims that Buffett’s secret can be explained only if one looks beyond the theory of investing. The success’ major driver is the transformation of Buffett’s name into a superbrand of mergers and acquisitions and Buffett’s hands-off policy with respect to the acquired companies. As a result of such an approach Buffett enjoys opportunities to buy first-class companies at moderate prices and keep key managers responsible for value creation.